Estimation of Evaporation from the Surface Water of the Gulf of Aqaba using Band 10 Onboard Landsat 8 - oroud, Ibrahim M.; altabeiri, Zeinab Shehadeh Ahmad (Dirasat: Human and Social Sciences, 2023)
Objectives: Surface temperature and evaporation are important geophysical parameters because of their close linkage to the energy balance and the hydrological cycle across the surface- atmosphere boundary of the globe. The aim of this study is to estimate surface temperature and evaporation rates across the Gulf of Aqaba using a Dalton-type equation. Methods: Band 10 onboard Landsat 8 was used to retrieve the brightness temperature, and the effect of the atmosphere on the retrieved surface temperature (SST) was corrected using the Radiative Transfer Equation. The retrieved SST was combined with near surface meteorological data to estimate daily evaporation from the Gulf of Aqaba using a Dalton- type equation. Results: Results show that the highest SST temperature was recorded in August, reaching 27.8 OC, while the lowest temperature of 16.7 OC was observed in January. Calculations of evaporation using a Dalton-type equation indicate that evaporation ranged from a minimum of 2.06 mm/day in November to 5.54 mm/day in June. Conclusions: The combination of high evaporation along with the meagre amount of freshwater input contributes to the high salinity observed in the Gulf of Aqaba compared to open seas and oceans.